2016
DOI: 10.1038/srep32478
|View full text |Cite
|
Sign up to set email alerts
|

Screening of SOD1, FUS and TARDBP genes in patients with amyotrophic lateral sclerosis in central-southern China

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease affecting motor neurons of the brain, brainstem and spinal cord. To date, mutations in more than 30 genes have been linked to the pathogenesis of ALS. Among them, SOD1, FUS and TARDBP are ranked as the three most common genes associated with ALS. However, no mutation analysis has been reported in central-southern China. In this study, we sequenced SOD1, FUS and TARDBP in a central-southern Chinese cohort of 173 patients with ALS (15 famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…In this study, among the 7 unrelated SOD1 - and FUS -negative ALS families, we detected 2 TARDBP mutations (c.1009A > G, p.M337 V and c.1042G > T, p.G348C) in 5 families. Importantly, 4 families carried the same TARDBP mutation, c.1009A > G, p.M337 V. Hou L et al screened SOD1 , TARDBP , and FUS gene mutations in ALS patients from central-southern China and revealed that SOD1 (20%) and FUS (13.3%) mutations were the main causal mutations in familial ALS, but they did not detect any TARDBP -linked ALS families [ 9 ]. In a Brazilian research centre, Chadi G et al reported that the most common gene mutations in familial ALS were VAPB (43.6%), C9orf72 (12.8%), and SOD1 (7.7%), whereas no FUS or TARDBP mutations were detected in any familial ALS subjects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among the 7 unrelated SOD1 - and FUS -negative ALS families, we detected 2 TARDBP mutations (c.1009A > G, p.M337 V and c.1042G > T, p.G348C) in 5 families. Importantly, 4 families carried the same TARDBP mutation, c.1009A > G, p.M337 V. Hou L et al screened SOD1 , TARDBP , and FUS gene mutations in ALS patients from central-southern China and revealed that SOD1 (20%) and FUS (13.3%) mutations were the main causal mutations in familial ALS, but they did not detect any TARDBP -linked ALS families [ 9 ]. In a Brazilian research centre, Chadi G et al reported that the most common gene mutations in familial ALS were VAPB (43.6%), C9orf72 (12.8%), and SOD1 (7.7%), whereas no FUS or TARDBP mutations were detected in any familial ALS subjects [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other inflammatory markers have shown varying results, such as C reactive protein (CRP), which showed no differences in plasma (132) or whole blood (60) at baseline. In serum, CRP was increased in ALS and did not associate with ALS risk or survival in one study (133), but correlated with ALSFRS-R and survival in another (134).…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…A recent analysis of trial data from over 1,200 people with ALS found strong longitudinal correlations between serum creatinine and ALSFRS-R score, muscle strength, and overall mortality, indicating that using serum creatinine in trials over 18 months in length would allow a reduction in sample size by 21.5% (141). Lending further support to this pathway as a useful biomarker of muscle denervation, serum creatine kinase (CK) is increased in plasma (132), and serum (140, 142) and correlates with survival in some studies (140, 142). This discrepancy may be attributed to differing rates of disease progression.…”
Section: Muscle Denervation Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroradiological examinations for example MRI, was assessed with patients diagnosed as probable or possible AD and FTD in this study. We have excluded AD, FTD and ALS patients carrying disease-causing gene like PSEN1, PSEN2, APP, MAPT, GRN, C9orf72, TREM2, CHCHD10, SOD1, TARDBP, FUS (3,(16)(17)(18)(19)(20). Additionally, the APOE genotype was available for all AD patients.…”
Section: Methodsmentioning
confidence: 99%